External Filtered Modes of a Quantum Dot Laser Under the Influence of Double-Filtered Optical Feedback - Mahdi, Alaa S.; Husseini, Hussein B. Al (International Journal of Membrane Science and Technology, 2023)
When semiconductor lasers SLs are exposed to filtered optical feedback (FOB), they behave in two different ways. Under weak or strong feedback, the first is a singularly stable longitudinal mode with a small linewidth. The second is the so-called coherence breakdown condition, which also includes low frequency fluctuations (LFF) and chaotic oscillations. The latter has received a lot of attention recently due to the possible uses of chaotic lasers in chaotic lidar, covert communications, and chaotic correlation time-domain optical reflectometers, while the former has received a lot of research in recent years. We investigate the behavior of a quantum dot (QD) semiconductor laser subject to FOF from two separate external cavities both, numerically and experimentally. Our findings show that the second FOF allows for rich adjustment of the laser frequency. Our analysis of double-filtered optical feedback (DFOF) lasers is on fundamental solutions, sometimes referred to as continuous waves (CW) or external filtering modes (EFM), which result in a QD laser output with constant amplitude and frequency. The time delay suppression is dependent on the spectral width  of the filter and how far it is from the solitary laser frequency, according to numerical calculations.